2022
DOI: 10.5114/pjr.2022.117593
|View full text |Cite
|
Sign up to set email alerts
|

Local recurrence of renal cell carcinoma after partial nephrectomy: applicability of the apparent diffusion coefficient of MRI as an imaging marker – a multicentre study

Abstract: Purpose The goal of the study was an assessment of the diagnostic performance of diffusion-weighted images (DWI) and apparent diffusion coefficient (ADC) of magnetic resonance imaging (MRI) in distinguishing local recurrence (LR) of renal cell carcinoma (RCC) from benign conditions after partial nephrectomy. Material and methods Thirty-nine patients after partial nephrectomy for solid RCC were enrolled in the study. Patients were followed up using MRI, which included DW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
1
0
2
Order By: Relevance
“…This study showed that the ADC was valuable in predicting the absence of recurrence or metastasis in the young breast cancer patients, with an AUC of 0.784 (95% CI: 0.630–0.937, P=0.007). Studies on patients with other malignancies have also shown that the ADC was associated with recurrence or metastasis ( 17 - 19 ). It can be seen from the above that the ADC of young breast cancer patients was reduced, which indicated that the tumor cell density of young breast cancer patients was high, and it was related to the poor prognosis of young breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that the ADC was valuable in predicting the absence of recurrence or metastasis in the young breast cancer patients, with an AUC of 0.784 (95% CI: 0.630–0.937, P=0.007). Studies on patients with other malignancies have also shown that the ADC was associated with recurrence or metastasis ( 17 - 19 ). It can be seen from the above that the ADC of young breast cancer patients was reduced, which indicated that the tumor cell density of young breast cancer patients was high, and it was related to the poor prognosis of young breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Трактування лабораторної діагностики у вагітних є неоднозначним і потребує обов'язкового співставлення з клінічними даними та результатами сонографічного обстеження, оскільки багато показників у вагітних є підвищеними також і в нормі або при патологіях вагітності, не пов'язаних з гострими інфекційними захворюваннями [15]. Для випадків, які потребують подальшої диференційної діагностики може бути застосована магнітно-резонансна томографія для обстеження нирок при консилярному рішенні лікарів [16][17][18]. У пацієнтки представленого випадку також є анемія, що вважається фактором ризику важкого перебігу COVID-19 [19].…”
Section: рис2 макроскопічний вигляд плаценти плацента червоно-синюшно...unclassified
“…. У таких випадках метод магнітно-резонансної томографії може стати неінвазивною альтернативою ультразвуку для вагітних жінок, особливо коли діагноз є неоднозначним, при умові доступності цього методу та урахуванням спільно прийнятого рішення з пацієнткою та її гінекологом в оцінці клінічної ситуації[26][27][28]. Таким чином, комплексне поєднання різних методів діагностики -лабораторної та радіологічної, дозволяє віддиференціювати фізіологічний гідронефроз від інших ускладнень сечовидільного тракту Therefore, the presentation of a series of such cases is complementary to the base of scientifi c research, taking into account that a woman's body is exposed to both hormonal and functional-constitutional changes of the state of pregnancy itself, as well as factors of physiological hydronephrosis and acute quarantine infectious disease.…”
unclassified